Abstract 220: Transradial Access Versus Transfemoral Approach for Carotid Artery Stenting: A Systematic Review and Meta‐analysis - Aaron Rodriguez‐Calienes; Fabian A. Chavez‐Ecos; David Espinosa‐Martinez; Diego Bustamante‐Paytan; Nagheli Fernanda Borjas‐Calderón; Milagros Galecio‐Castillo; Juan R. Vivanco‐Suarez; Waldo Guerrero R; Santiago Ortega‐Gutierrez (Stroke: Vascular and Interventional Neurology)
Introduction Carotid artery stenting (CAS) has emerged as a viable alternative to carotid endarterectomy for managing carotid artery stenosis in high‐risk patients (1). While the transfemoral arterial approach (TF) remains the preferred method, it is associated with inherent limitations and potential complications (2‐4). Consequently, exploring the transradial artery access (TR) as a potential option becomes crucial in optimizing patient outcomes and procedural success rates. Limited data exists comparing the outcomes of TR approach in CAS to TF approach. This study aims to systematically review and meta‐analyze the outcomes and complication rates between TR and TF access for CAS. Methods A systematic electronic search was conducted in four databases up to May 10th, 2023. Studies with randomized or non‐randomized designs, involving CAS through TR or TF approach, were included. Outcomes of interest were stroke, transient ischemic attack (TIA), death, myocardial infarction (MI), and access site complications. A meta‐analysis was performed, analyzing pooled odds ratios (ORs) and 95% confidence intervals (CI) to assess the effect size of the vascular access approaches. Results Six studies with a total of 6,917 patients were included, out of which 602 (8.7%) underwent the TR approach, and 6,315 (91.3%) underwent the TF approach. Meta‐analysis results showed no significant difference in stroke occurrence between TR and TF groups (TR: 1.7% vs. TF: 1.9%; OR = 0.98; 95% CI 0.49 – 1.96; I2 = 0%). Similarly, no significant difference was found in death (TR: 1% vs. TF: 0.9%; OR = 0.95; 95% CI 0.38 – 2.37; I2 = 0%), MI (TR: 0.2% vs. TF: 0.3%; OR = 1.53; 95% CI 0.20 – 11.61; I2 = 0%), TIA (TR: 0.4% vs. TF: 1%; OR = 0.46; 95% CI 0.11 – 1.95; I2 = 0%), and access site complications (TR: 2.2% vs. TF: 1%; OR = 0.97; 95% CI 0.48 – 1.98; I2 = 0%). Conclusion In the comparison of TR and TF approaches for CAS, no significant differences were observed in stroke, death, MI, TIA, or access site complications. TR approach shows promise as an alternative method for CAS, offering potential benefits without increased risk of complications. However, further studies are needed to confirm these findings and establish guidelines for optimal access site selection.